2019
DOI: 10.1111/jvim.15665
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Doppler spectrum of hepatic veins and correlation with structural and functional variables of the right ventricle in healthy dogs

Abstract: Background: Spectral Doppler assessment of hepatic veins may provide information on heart function. Hypothesis/Objectives: To assess the normal pattern of hepatic venous flow using spectral Doppler ultrasound examination; to correlate this information with structural and functional variables of the right ventricle (RV), and to analyze the impact of age, sex, body weight quartiles, heart rate, cardiac rhythm, and systolic arterial pressure on the results in healthy dogs.Animals: Sixty-five healthy dogs.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…One previous study compared Doppler variables of hepatic venous flow to right ventricular systolic and diastolic variables in dogs and determined velocity of spectral waves could be correlated with functional indices of the RV such as TAPSE, FAC% and longitudinal myocardial velocity (S′). However, this study did not determine the size of the hepatic vessels 51 . A similar study examined the velocities of the hepatic A, S, D, and V waves in dogs with PH.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One previous study compared Doppler variables of hepatic venous flow to right ventricular systolic and diastolic variables in dogs and determined velocity of spectral waves could be correlated with functional indices of the RV such as TAPSE, FAC% and longitudinal myocardial velocity (S′). However, this study did not determine the size of the hepatic vessels 51 . A similar study examined the velocities of the hepatic A, S, D, and V waves in dogs with PH.…”
Section: Discussionmentioning
confidence: 89%
“…However, this study did not determine the size of the hepatic vessels. 51 A similar study examined the velocities of the hepatic A, S, D, and V waves in dogs with PH. Although this study indicated weak to moderate correlations with functional variables of the RV, a D wave cut‐off of 11.6 cm/s had a sensitivity of 100% and specificity of 35% to differentiate patients with severe PH from healthy dogs.…”
Section: Discussionmentioning
confidence: 99%